E-WAY GAME E-Way Game Platform as a Digital Media to Train Critical Thinking in Early Childhood - Sutama, I Wayan; Wuri Astuti; Nur Anisa; Pramono; Alifia Lailatur Rahmi; Rosyidatun Nafi’ah (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
In the digital era, children are increasingly familiar with technology, but there are still few technology-based media specifically designed for educational purposes, particularly those aimed at developing critical thinking skills. Most existing digital media are entertainment games without educational content. Although technological advancements have been rapid, research underpinning the development of educational digital media to foster critical thinking skills in early childhood remains limited. This creates a gap between field needs and the availability of effective solutions. The goal of this research is to develop an effective E-Way Game platform as a digital medium to stimulate critical thinking skills in early childhood. The research subjects consist of 2 material expert validators, 2 media expert validators, 3 users (teachers), and 20 children (aged 4–6 years). The research and development method employs the ADDIE model. Data collection techniques include observation sheets and questionnaires, with data analysis conducted using descriptive quantitative methods. The results of the media expert validation test scored 88% (very feasible), the material validation test scored 94% (very feasible), the user test scored 85% (very feasible), the small group test scored 86% (very feasible), and the large group test scored 94% (very feasible). Based on these results, it can be concluded that the E-Way Game platform is highly feasible for use in improving children's critical thinking skills. The implications of this media development serve as a reference for digital learning media aimed at stimulating critical thinking skills in children aged 4–6 years.